Implementation of Training and Human Resource Development Programs in Improving Employee Performance (Survey on PT Citra Kendedes Cake and Bakery Malang City) - Lusiana Ega; Gunawan, Cakti Indra; Anung Prasetyo Nugroho (International Research & Development for Human Beings (IRDH), 2025)
Training and development of human resources (HR) are strategic assets in improving employee competence, reducing employee turnover, and strengthening adaptability to technological developments. This study examines the individual impact of training and HR management and the combined effect of these factors on employee performance at PT Citra Kendedes Cake and Bakery, Malang City. The research method used a quantitative approach through a survey with a questionnaire instrument filled out by 36 respondents. The training program (H1) partially significantly improves employee performance at PT Citra Kendedes Cake and Bakery Malang. This is evidenced by the significance value of 0.000 (<0.05) and the t-count value (4.287), which is higher than the t-table (2.034). HR development (H2) also has a partially significant effect on employee performance, with a significance level of 0.006 (<0.05) and a t-count value (2.967) exceeding the t-table (2.034). Simultaneously, the combination of training and HR development programs has a significant effect on employee performance, indicated by the significance value of the F-test of 0.000 (<0.05) and the F-count (42.471), which far exceeds the F-table (3.28). In addition to improving technical competencies, training creates an innovative and adaptive work environment, which is key to organizational sustainability amid technological and market disruptions.